What is the impact of green credit on technical innovation in renewable energy? The policy-accommodating practices of businesses - Guang Chen; Junfeng Wang; Johnson Kane (Energy Strategy Reviews)
The rapid development of renewable energy technologies is critical to achieving environmental sustainability, yet the role of financial mechanisms like green credit in fostering such innovation remains underexplored. This study examines the impact of green credit on the technical innovation of clean energy enterprises (TICEE) in China from 2010 to 2022, with a particular focus on the moderating effect of corporate policy catering behavior (CPCB). Employing a moderated mediation model, the analysis reveals that green credit significantly enhances technical innovation in renewable energy firms, with debt structure and corporate innovation acting as key mediating factors. The results also show that CPCB strengthens the positive relationship between green credit and TICEE, further accelerating innovation. Statistical analysis confirms the substantial role of green credit in driving advancements in clean energy technologies, while CPCB enhances enterprises' responsiveness to policy incentives. These findings underscore the importance of green credit policies in promoting technological progress and sustainable business practices, providing valuable insights for policymakers aiming to support renewable energy innovation and economic growth.